Enhancing fourth-grade fractional learning through Powtoon integrated audiovisual mathematics media - Agustin, Nia; Junaedi, Akhmad (Indonesian Journal of Science and Mathematics Education, 2024)
The background of this research highlights the need to integrate technology into education to improve learning experiences and outcomes. The main aim is to develop effective learning media to overcome students' difficulties in understanding grade IV fraction material. This research employed the research and development (R and D) methodology with the Borg and Gall model for designing, validating, and testing media. The validation score was 91.6% from media experts and 89.2% from material experts. Therefore, the product developed was feasible. The research results also show that Powtoon-based learning media significantly increases student motivation and learning outcomes, with an N-gain value of 0.6059 in the small group trial and 0.6331 in the large group trial with the moderate improvement category. The implications show that integrating Powtoon media into mathematics education can create a more exciting and effective learning environment, thus supporting students’ academic achievement.